2019
DOI: 10.1080/2090598x.2019.1677296
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy in patients with high prostate-specific antigen: Is it worth considering? A systematic review

Abstract: Objective: To address the question of whether antibiotic therapy can obviate the need for prostate biopsy (PBx) in patients presenting with high prostate-specific antigen (PSA) levels.Methods: With the increase in unnecessary PBx in men with high PSA levels, a systematic review was performed according to the Cochrane Reviews guidelines and in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Results: The literature search yielded 42 studies, of which 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Clavien-Dindo complications grade 3 to 5 have never occurred. The distribution of adverse events in this study is truly interesting since, in front of a meaningful higher rate of complications, there were no serious events requiring medical intervention while most of the authors, on the contrary, report some complications of grade 3 or even more in their series [ 10 , 15 , 18 , 21 , 35 , 36 ]. Some authors have chosen not to report complications below grade 3, evidently considering them not significant [ 7 , 29 ].…”
Section: Discussionmentioning
confidence: 65%
“…Clavien-Dindo complications grade 3 to 5 have never occurred. The distribution of adverse events in this study is truly interesting since, in front of a meaningful higher rate of complications, there were no serious events requiring medical intervention while most of the authors, on the contrary, report some complications of grade 3 or even more in their series [ 10 , 15 , 18 , 21 , 35 , 36 ]. Some authors have chosen not to report complications below grade 3, evidently considering them not significant [ 7 , 29 ].…”
Section: Discussionmentioning
confidence: 65%
“…In a recent meta-analysis of 31 different series including 8 randomized clinical trials, more than 2 weeks of antibiotic therapy was reported to be beneficial for detecting PCa when PSA was <20 ng/mL. 16 reported to show a PSA decrease over 8 weeks after alpha-blocker administration, 12 even compared with the range of 17%-80% in PSA decrease of antibiotic studies with shorter-term duration. 15 Because the majority of the subject who agreed to delay their biopsy by initial presentation was willing to go to refuse the planned biopsy after the normalization of PSA level from the baseline, their cancer status was not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the controversy surrounding the value of antibiotics in reducing higher PSA levels, some urologists in daily practice often prescribe antibiotics before prostate biopsy to men with newly elevated PSA levels. The reduction of PSA levels after the administration of antibiotics can identify patients whose prostate biopsy can be avoided (Özman O & Talat Z, 2019;Taha et al, 2020).…”
Section: Changes In Psa Level Values With Ciprofloxacin Administratio...mentioning
confidence: 99%
“…The use of antibiotics in patients with elevated PSA levels of >4 ng/mL may avoid prostate biopsy examinations. The decrease in PSA levels with the use of antibiotics varies from 17% to 80% of cases (Taha et al, 2020). Therefore, researchers are interested in conducting research on the effect of antibiotic administration on PSA levels of patients with suspected prostate cancer.…”
Section: Introductionmentioning
confidence: 99%